National Prosecutors Survey, 1990 ([Verlag nicht ermittelbar], 1992)
This survey queried chief prosecuting attorneys of state prosecutorial districts (district attorneys, commonwealth attorneys, etc.) about the prosecution of felony cases within their jurisdictions during 1989-1990. Questions regarding the prefiling, filing, and pretrial stages of felony prosecution asked about policies limiting the time for plea negotiations, the role of the grand jury, how felony cases were screened, and the amount of time that usually elapsed before the prosecutor was notified of persons arrested for a felony. Prosecutors were also asked to report the percentage of court case filings by grand jury indictment, by information following a preliminary hearing, or by other means, and the percentage of felony cases processed by a court of general jurisdiction, a felony court, or other court(s). The trial stage of felony prosecution was covered by questions about the conduct of voir dire examination of prospective jurors, limits on time allowed to commence trial, the number of permitted peremptory challenges, who was responsible for notifying government witnesses to appear in court, whether the prosecution had the right to request a jury trial, whether the jurisdiction's felony court discouraged motions on trial date that would delay trial, and whether the felony court normally granted a continuance on trial date to permit additional time for plea negotiations. Questions on felony sentencing and appeals asked whether the prosecutor was usually present at felony sentence proceedings, whether the judge usually ordered a presentence report, whether victim information was requested or provided by the court, whether the prosecutor normally recommended a type or duration of sentence to be imposed, whether police, victims, or witnesses were notified of the disposition of felony cases, whether the prosecutor was involved in various types of appellate work, and whether the prosecutor had any right of appeal from rulings on motions, from sentences, and from determination of guilt or innocence. General information gathered by the survey includes the number of jurisdictions contained in the prosecutorial district, the number of attorneys and investigators employed in the sampled jurisdiction and in the prosecutorial district as a whole, the length of the prosecutor's term of office, the number of law enforcement agencies that brought arrests into the jurisdiction's court, how much of the prosecutor's felony caseload was assigned on a vertical basis, the kinds of nonfelony matters the prosecutor had responsibility for or jurisdiction over (e.g., family and domestic relations, mental commitments, environmental protection, traffic, etc.), whether the office of prosecutor was an elective position, and whether it was a full- or part-time position. Other general items include whether any felony defendants were provided an attorney on the grounds of indigency, whether, in criminal cases involving both state and federal jurisdiction, the prosecutor would ordinarily be cross-designated to represent the prosecutor in both courts, whether the prosecutor's office contained a "career criminal" unit, whether the state's attorney general was entitled to try cases in the jurisdiction's felony court, which types of criminal history data normally were of practical value in felony prosecution, and who supervised the probationer in most cases of adult felons sentenced to probation.